南极产低温几丁质酶菌株的筛选及分子鉴定 - 曾润颖; 林念炜; 连明珠; 张锐 (2006)
从南极普里兹湾深海底泥样品中分离得到一批嗜冷细菌,对这些嗜冷细菌进行了产几丁质酶菌株的筛选,对其中一株具有较高产酶活性的菌株AC167所分泌的几丁质酶进行了性质分析,并通过16S rDNA序列分析进行了菌株的分子鉴定。该菌株最适生长温度为10℃,最高生长温度为25℃,是典型的嗜冷菌,经16S rDNA序列比较及系统发育分析鉴定为假单胞菌属(Pseudomonas)。该菌株只在低于25℃的条件下分泌几丁质酶,酶的最适反应温度为30°C,属于低温酶。 An amount of psychrophilic bacteria was isolated from deep sea sediment collected from Prydz Bay,Antarctica.The strain AC167,which showed high cold-active chitinase activity,was screened from these bacteria.It was identified as a Pseudomonas species by 16S rDNA sequence comparison.The optimal and highest temperatures for the growth of Pseudomonas strain AC167 were 10℃ and 25℃ respectively,indicating that it was a typical psychrophilic bacterium.The chitinase produced by Pseudomonas strain AC167 belonged to cold-active enzyme because it was most active at 30℃ and was secreted only at temperatures under 25℃. 国家自然科学青年基金资助项目(4406029);; 国家海洋局青年基金资助项目(98310)